The specific heat and the radial thermal expansion of bundles of single-walled carbon nanotubes - Bagatskii, M.I.; Barabashko, M.S.; Dolbin, A.V.; Sumarokov, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The specific heat at constant pressure C(T) of bundles of single-walled carbon nanotubes (SWNTs) closed at their ends has been investigated in a temperature interval of 2–120 K. It is found that the curve C(T) has features near 5, 36, 80, and 100 K. The experimental results on the C(T) and the radial thermal expansion coefficient αR(T) of bundles of SWNTs oriented perpendicular to the sample axis have been compared. It is found that the curves C(T) and αR(T) exhibit a similar temperature behavior at T > 10 K. The temperature dependence of the Grüneisen coefficient γ(T) has been calculated. The curve γ(T) also has a feature near 36 K. Above 36 K the Grüneisen coefficient is practically independent of temperature (γ ≈ 4). Below 36 K γ(T) decreases monotonically with lowering temperature and becomes negative at T < 6 K.